Assessment of Apoptotic Activity Dysregulation and Oxidative Stress in the Development of Epithelial Ovarian Cancer: A Case-Controlled Descriptive Analysis - (:unkn) unknown (KARGER, 2016)
Aim: In the present study, we aimed to assess whether oxidative stress and apoptotic activity play a role in the development of epithelial ovarian cancer (EOC). Methods: The study group included patients with EOC (n = 26) and benign ovarian tumour (BOT) (n = 25), while 30 healthy women were employed as a control group. Venous blood samples were drawn to evaluate oxidative stress parameters and serum M30/M65 antigen levels before surgery. In addition, blood samples were taken for the second time on postoperative day 8 to analyse whether the postoperative tumour load was decreased. Results: When the groups were assessed regarding oxidative stress, the highest values were detected in patients with EOC. Serum M30/M65 levels were found to be higher in patients with EOC when compared to the other groups (p < 0.001). A significant decrease was determined in the M30/M65 levels of serum samples taken on postoperative day 8 from the patients in the EOC and BOT groups (p < 0.001). Conclusion: Our results suggest that dysregulation of apoptotic activity could be effective in the development of ovarian tumoural tissue, whereas oxidative stress could be effective in malignant transformation. (C) 2015 S. Karger AG, Basel
Keywords: Epithelial ovarian cancer; Benign ovarian tumour; Cytokeratin 18; M30/M65; Oxidative stress; M65 VALUES; SERUM M30; EXPRESSION; PROGNOSIS; PROTEINS; DISEASE